1994
DOI: 10.1111/j.1460-9568.1994.tb00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Compound Action Potential: an Electrophysiological, Biochemical and Morphological Study of Early Events in Axonal Degeneration in the C57BL/Ola Mouse

Abstract: In the C57BL/Ola (Ola) mouse strain there is a marked slowing of axonal disintegration during Wallerian degeneration. The locus of the mutation controlling this phenomenon (slow Wallerian degeneration--Wlds) has been mapped to chromosome 4, and its protective effect decreases with advancing age. Using biochemical, electrophysiological and histological techniques, the present study was undertaken to determine whether neurofilament phosphorylation and stability are altered or whether calcium-activated proteases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 43 publications
4
39
0
Order By: Relevance
“…We confirmed that axonal degeneration in vivo and in vitro in 6N nerves was comparable, with ϳ2.5% of the CAP (relative to control) remaining at 2 d, as previously reported (Tsao et al, 1994). The act of axotomy and removing the nerves for culturing was found to reduce the CAP A wave by ϳ30% within 3 hr, after which the nerve was stable for the next 21 hr ( Fig.…”
Section: Axonal Degeneration In Vivo and In Vitrosupporting
confidence: 90%
See 4 more Smart Citations
“…We confirmed that axonal degeneration in vivo and in vitro in 6N nerves was comparable, with ϳ2.5% of the CAP (relative to control) remaining at 2 d, as previously reported (Tsao et al, 1994). The act of axotomy and removing the nerves for culturing was found to reduce the CAP A wave by ϳ30% within 3 hr, after which the nerve was stable for the next 21 hr ( Fig.…”
Section: Axonal Degeneration In Vivo and In Vitrosupporting
confidence: 90%
“…In Wld mice the first electrophysiologically detectable event in Wallerian degeneration is axonal inability to continue conducting CAPs although the morphology remains relatively preserved (Tsao et al, 1994). Via monitoring the disappearance of CAPs and axonal morphology, this study also demonstrated that axonal degeneration had similar rates in vivo and in vitro.…”
mentioning
confidence: 53%
See 3 more Smart Citations